Reconstruction of Autobiographical Memories of Violent Sexual-Affective Relationships Through Scientific Reading on Love: A Psycho-Educational Intervention to Prevent Gender Violence - Racionero-Plaza, Sandra; Ugalde-Lujambio, Leire; Puigvert, Lídia; Aiello, Emilia (Frontiers in Psychology, 2018)
Violence in sexual-affective relationships among teens and young people is recognized as a social, educational, and health problem that has increased worldwide in recent years. Educational institutions, as central developmental contexts in adolescence, are key in preventing and responding to gender violence through implementing successful actions. In order to scientifically support that task, the research reported in this article presents and discusses a psycho-educational intervention focused on autobiographical memory reconstruction that proved to be successful in raising young women’s critical consciousness about the force of the coercive dominant discourse upon sexual-affective experiences and memories. We examined among a sample of young women (n = 32, age range 17-30) whether reading a scientific text about love, the Radical Love book, modified autobiographical memories of violent sexual-affective relationships in line with preventing future victimization. This group was compared with a control group (n = 31, age range 17-30). Memory reports were collected before and after the reading and coded to analyze their content, both quantitatively and qualitatively. Memory quality features were assessed with the Memory Quality Questionnaire. A focus group was also conducted to examine the personal impact of the intervention on participants. Compared with controls, the experimental group had stronger critical memories (of episodes involving violence), an average decrease in positive emotions induced by recall, and an average increase in negative emotions. The results show the effectiveness of the reading intervention designed in relation to gender violence prevention, as they indicate the ability of the psycho-educational action to debilitate the force of the coercive dominant discourse in young women’s memories. The findings both advance knowledge on the reconstructive nature of autobiographical memories of violent sexual-affective relationships in female youth and indicate the potential of memory-based interventions as an instrument to prevent and reduce gender violence in school contexts. Teachers and teaching staff, and educational psychologists, among others, can benefit from these results by expanding the tools they have to address gender violence among female adolescents and youth.